(untitled) - Johnson, Eric (Indianapolis, Ind., 2008)
If you are a support professional who sets up, maintains, and troubleshoots desktop applications on Windows Vista, now you can build your skills and prepare for exam 70-623, MCITP: Supporting and Troubleshooting Applications on a Windows Vista Client for Consumer Support Technicians, the required exam for achieving certification as an MCITP: Consumer Support Technician. Inside this comprehensive study guide you'll find full coverage of all exam objectives, practical hands-on exercises, real-world scenarios, challenging review questions, and more. For Instructors: Teaching supplements are available for this title.
Keywords: Electronic data processing personnel,Microsoft software,Nhà xử lý dữ liệu điện tử,Phần mềm Microsoft; Certification,Examinations,Chứng nhận,Sự nghiên cứu